What is behind the closed door? A case illustration of working with social isolation in adolescents using Adaptive Mentalization‐Based Integrative Treatment (AMBIT). Issue 5 (22nd April 2021) - Jensen, Stefan Lock; Bo, Sune; Vilmar, Janne W.
Abstract: Background : In this paper, we outline our approach to dealing with complex social isolation by presenting a network treatment approach named Adaptive Mentalization‐Based Integrative Treatment (AMBIT). Method : We describe the AMBIT approach, what elements it consists of, and we explain how we employed this method in the case of a 17‐year‐old boy referred to our child and adolescent psychiatric clinic, who isolated himself from the world. Results : We emphasize in which ways the specific network approach pertinent to the AMBIT approach was helpful in this complex case. Furthermore, we describe and reveal our insecurities and doubts related to our interventions and the general treatment process and point to why the AMBIT network approach and the interventions were crucial in this case. Discussion : We argue that the boy could not have been helped out of his social isolation within the conventional child and adolescent psychiatric system without engaging and establishing an integrated professional network from many sectors.